Teacher’s Type D Personality and Chinese Children’s Hyperactive Behaviors: Moderation Effect of Parental Type D Personality and Mediation Effect of Teacher–Student Relationship - He, Guan-Hao; Strodl, Esben; Liu, Li; Ruan, Zeng-Liang; Yin, Xiao-Na; Wen, Guo-Ming; Sun, Deng-Li; Xian, Dan-Xia; Jiang, Hui; Jing, Jin; Jin, Yu; Wu, Chuan-An; et al. (Frontiers in Psychology, 2019)
This study aimed to explore the association between teacher’s Type D Personality (TDP) and children’s hyperactive behaviors, along with the moderation effect of parental TDP and the mediation effect of the teacher-student relationship. In this prospective study, a total of 25852 children were surveyed from 2014 to 2016 in Longhua District of Shenzhen, China, and followed up 1 year later. At baseline, parents provided data on parental TDP, children’s hyperactive behaviors, while teachers reported on their TDP. At follow-up, parents provided data on children’s hyperactive behaviors again, and teachers described their relationship with each student. Two-level multilevel logistic models were conducted to assess the influence of a teacher’s TDP, parental TDP and their interaction on children’s hyperactive behaviors. Mediation analysis was used to examine the mediating role of the teacher-student relationship. Results indicated that teachers’ TDP was not a significant predictor of children’s hyperactive behaviors after 1 year in kindergarten. Conversely, maternal and paternal TDP were prospectively and positively associated with children’s subsequent hyperactive behaviors. However, the children with a TDP teacher, TDP mother, and/or TDP father had higher risk of hyperactive behaviors than those with either TDP teacher or TDP mother or TDP father. In addition, the teacher-student relationship was not a significant mediator between teacher’s TDP and children’s hyperactive behaviors. Further researchers may consider the effect of combination of teacher’s TDP, maternal TDP and paternal TDP on hyperactive behaviors in children in further study.